Розірвання трудового договору у разі скасування допуску до державної таємниці: проблемні питання - Середа О. Г.; Красюк Т. В. (НДІ правового забезпечення інноваційного розвитку НАПрН України; Право, 2022)
У статті висвітлено проблемні питання, пов’язані із розірванням трудового договору з ініціативи роботодавця в разі відмови у доступі до державної таємниці або скасування допуску до державної таємниці, якщо виконання покладених на працівника обов’язків вимагає доступу до такої таємниці. Доведено, що роботодавець повинен заздалегідь повідомляти працівника про те, що допуск його до державної таємниці несе певні, встановлені законом, обмеження прав, а також він повинен бути ознайомлений з встановленою мірою відповідальності за порушення законодавства про державну таємницю. Звернено увагу на те, що чинне законодавство України не передбачає чіткого переліку посад і робіт, які потребують отримання доступу до інформації, що становить державну таємницю. Аргументовано неможливість створення диференційованої тарифікації посад, які передбачають роботу із секретною інформацією. Запропоновано виключити таку підставу припинення трудового договору, як скасування допуску до державної таємниці, з переліку підстав розірвання трудового договору за ініціативою роботодавця і включити її до підстав припинення трудових відносин, що не залежать від волі сторін трудового договору. Сформульовано пропозиції до Закону України «Про державну таємницю». Для отримання допуску до державної таємниці окремі суб’єкти, такі, як Президент України, Голова Верховної Ради України, Прем’єр-міністр України та інші члени Кабінету Міністрів України, Голова Верховного Суду, Голова Конституційного Суду України, Генеральний прокурор, Голова Служби безпеки України, Голова та інші члени Рахункової палати, народні депутати України, повинні мати не лише письмове зобов’язання щодо збереження державної таємниці, а й проходити перевірку в спеціальному органі. Відмова від проходження спеціальної перевірки є беззаперечною підставою відмови у наданні допуску до державної таємниці. Problem settings. Problems of protection of state secrets have become especially relevant in recent years, during the deep socio-economic transformations in Ukraine, when, on the one hand, new threats to national security, and on the other, and this must, unfortunately, admit protection of state secrets not always carried out properly. The existence of problems in this important area for the protection of the state is evidenced by the frequent labor disputes, including over various conflicting aspects of access to and access to state secrets, which are considered in administrative courts. Therefore, the need for a careful revision of certain provisions of the law governing, in particular, the refusal to grant access to state secrets becomes obvious. Analysis of recent researches and publications. O. Bondar, L. Kupina, O. Semenyuk, A. Tsapenko, O. Yaroshenko studied the legal aspects of termination of the employment contract in connection with the revocation of access to state secrets. However, today we need new topical research, the search for modern approaches to regulatory issues of dismissal of the employee due to these circumstances. Target of research. The purpose of the article is to reveal the features of the termination of the employment contract in case of revocation of access to state secrets in Ukraine. Article’s main body. The article covers problematic issues related to the termination of the employment contract at the initiative of the employer in the case of denial of access to state secrets or revocation of access to state secrets if the duties of the employee require access to such secrets. Doctrinal definitions of the concept of «state secret» are analyzed. It is proposed the author’s definition of the term «state secret» which means a type of secret information that covers information in the area of defense, economics, science and technology, foreign relations, state security and law enforcement, the disclosure of which harms or threatens the national security of Ukraine and which is protected by the state in accordance with regulations. The authors reveal the content and features of the legal mechanism for granting and revoking access to state secrets. It is proved that the employer must inform the employee in advance that his admission to the state secret carries certain restrictions established by law and he must be acquainted with the established degree of responsibility for violating the law on state secrets. Attention is drawn to the fact that the current legislation of Ukraine does not provide a clear list of positions and jobs that require access to information that is a state secret. This is due to the fact that each company has its own characteristics and the degree of secrecy and nature of information and the degree of admission to it and the admission procedure itself. Therefore, it is hardly possible to apply the methods of systematization and differentiation due to the multiplicity of features, because it will be extremely difficult to foresee all the positions for charging. Conclusions. It is proposed to exclude such grounds for termination of employment contract as revocation of access to state secrets from the list of grounds for termination of employment at the initiative of the employer and include it in the grounds for termination of employment that do not depend on the will of the employment contract. It is determined that the mechanism of the procedure for granting access to state secrets in relation to certain subjects requires changes at the legislative level which will avoid real threats to the national security of our state. Proposals to the Law of Ukraine «On State Secrets» have been formulated. To obtain access to state secrets, certain entities, such as the President of Ukraine, the Chairman of the Verkhovna Rada of Ukraine, the Prime Minister of Ukraine and other members of the Cabinet of Ministers of Ukraine, the Chairman of the Supreme Court, the Chairman of the Constitutional Court of Ukraine, the Prosecutor General, the Security Service Ukraine, the Chairman and other members of the Accounting Chamber, the People’s Deputies of Ukraine, must not only have a written commitment to preserve state secrets but also be inspected by a special body. The refusal to pass a special inspection is an indisputable ground for refusing to grant access to a state secret.
Keywords: розірвання трудового договору; державна таємниця; допуск працівника до державної таємниці; інформаційна безпека; національна безпека; секретна інформація; інформація з обмеженим доступом; termination of the employment contract; state secret; admission of the employee to the state secret; information security; national security; secret information; information with limited access